Nehruvian Vision: Building a Strong and United India through Secularism, Democracy, and Development - Dr. Pawan Kumar (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Emphasizing modern ways of thinking, Jawaharlal Nehru led the nation-building of India. He kept promoting rational thinking in every field to boost the country’s welfare. Especially, he valued a person’s national citizenship above their religion or religious community. It meant that he gave importance to keeping politics and religion different and apart. Furthermore, all people, no matter their colour, caste or community, were supposed to respect the nation. So, the differences between castes, communities and religious groups started causing difficulties for India’s new states once the country became independent. For this reason, strong leadership acknowledged these shortcomings and took ways to complete the process of nation building. Jawaharlal Nehru stood at the forefront in this regard. He stood for India’s independence and remained at the helm of the nation until he died. This title clearly demonstrates Nehru’s method of building the nation by highlighting his devotion to democracy, secularism and growth. It points out that in Gandhi’s view, these beliefs were required for India to remain strong and united. “Nehruvian Vision” is used to explain the ideas and policies that Nehru introduced during his time as Prime Minister of India. Through the title, you can see the primary ideas in Nehru’s philosophy such as democracy, secularism and development. All in all, the chosen title reflects accurately how Nehru’s views helped India throughout the development of the nation.